2019
DOI: 10.1049/iet-epa.2019.0251
|View full text |Cite
|
Sign up to set email alerts
|

Review based on losses, torque ripple, vibration and noise in switched reluctance motor

Abstract: Some key features to be satisfied by electric motors catering a wide range of applications are high specific power, lower manufacturing cost, rugged construction, and fault‐tolerant operation. Switched reluctance motor is one such motor technology satisfying all the above requirements and is an emerging competitor to the induction and permanent magnet motors in domestic, industrial and electric vehicle applications. The present‐day research on this motor is moving towards improving efficiency at lower speeds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 144 publications
0
11
0
Order By: Relevance
“…Currently, most of the major rapier loom manufacturers in Europe have adopted permanent magnet synchronous motor (SRM) speed regulation systems with direct rotation structures, which simplify the mechanical structure and are more energy-saving and efficient than the frequency conversion speed regulation system [7][8]. Compared with permanent magnet synchronous motors, SRMs have a simple structure and a lower cost.…”
Section: Figure 2 Structure Diagram Of a Loommentioning
confidence: 99%
“…Currently, most of the major rapier loom manufacturers in Europe have adopted permanent magnet synchronous motor (SRM) speed regulation systems with direct rotation structures, which simplify the mechanical structure and are more energy-saving and efficient than the frequency conversion speed regulation system [7][8]. Compared with permanent magnet synchronous motors, SRMs have a simple structure and a lower cost.…”
Section: Figure 2 Structure Diagram Of a Loommentioning
confidence: 99%
“…Modifying winding arrangement can change the direction of the flux path, which affects the flux density of the machine. The phenomenon of flux reversals in the stator core back is one of the causes that affects the variation of the flux density in the SRM [14][15][16]. Therefore, minimizing the number of flux reversals occurring on the stator core back can decrease the core loss in SRM.…”
Section: Core Loss Based On Flux Reversalsmentioning
confidence: 99%
“…The flux reversal has a significant impact on the core loss of the SRM. Research on reducing flux reversal, such as [12][13][14][15][16], was implemented by modifying the shape of the stator. In this paper, the method to reduce the flux reversal will be discussed based on the winding arrangement.…”
Section: Introductionmentioning
confidence: 99%
“…Winding configuration, converter topologies, and some control strategies are also discussed. It has been reported that a multi-stack structure produces lower torque ripple [10,11]. Its concept is to create a more circular air-gap, which is why it is effective to reduce the torque ripple.…”
Section: Introductionmentioning
confidence: 99%